Ambivalensi di Tengah Pandemik Covid-19 Perspektif Bhakti Marga - Ida Bagus Putu Adnyana; I Nyoman Mandiasa (Sphatika: Jurnal Teologi, 2020)
The piodalan ceremony at the Pura Kahyangan Dalem Banjar Dakdakan was carried out in the midst of the Covid-19 pandemic by continuing to put forward the government's recommendations and implement and adhere to health protocols. Ambivalence occurs in the community due to this pandemic. There is such a variety of reasoning processes in society, ranging from the attitude of the community that takes Covid-19's pandemic lightly to the point that there are people overreacting in addressing this pandemic and leading to excessive fear (paranoids). This can occur as a result of the many issues circulating about this pandemic whose reality of truth is still being questioned and its validity and reliability have not been tested. The condition of society which is still low in critical reasoning makes it easy to be consumed by disinformation or hoax issues. The above problems will be examined based on the perspective of Bhakti Marga to be able to uncover ambivalence that occurs in the community related to the impact on social life and religious community, especially the people of Banjar Dakdakan and to find out the level of public reliability of the stakeholders in the Banjar Dakdakan region when carrying out the piodalan ceremony in the Pura Kahyangan Dalem Banjar Dakdakan.